Объяснение:
2HCl + Zn = ZnCl2 + H2↑
2H(+) +2e = H2(0) 1 в-ие
ок-ль
Zn(0) -2e = Zn(+2) 1 ок-ие
в-ль
2HCl + CaO = CaCl2 + H2O
2H(+) + 2Cl(-) + CaO = Ca(2+) + 2Cl(-)+ H2O
2H(+) + CaO = Ca(2+) + H2O
HCl + RbOH = RbCl + H2O
H(+) + Cl(-) + Rb(+) + OH(-) = Rb(+) + Cl(-) + H2O
H(+) + OH(-)= H2O
2HCl + Mg(OH)2 = MgCl2 + 2H2O
2H(+) + 2Cl(-)+ Mg(OH)2 = Mg(2+) + 2Cl(-) + 2H2O
2H(+) + Mg(OH)2 = Mg(2+) + 2H2O
HCl + AgNO3 = AgCl ↓+ HNO3
H(+) + Cl(-) + Ag(+) + NO3(-) = AgCl↓ + H(+) + NO3(-)
Ag(+) + Cl(-)= AgCl↓
H2 + Cl2 = 2HCl
H2(0) -2e = 2H(+) 1 ок-ие
в-ль
Cl2(0) +2e = 2Cl(-) 1 в-ие
ок-ль
Объяснение:
BaO + H2O = Ba(OH)2
BaO + H2O = Ba(2+) + 2OH(-)
Ba(OH)2 + 2HNO3 = Ba(NO3)2 + 2H2O
Ba(2+) + 2OH(-) + 2H(+) + 2NO3(-) = Ba(2+) + 2NO3(-) + 2H2O
H(+) + OH(-) = H2O
Ba(NO3)2 + H2SO4 = BaSO4 ↓+ 2HNO3
Ba(2+) + 2NO3(-) + 2H(+) + SO4(2-) = BaSO4↓ + 2H(+) + 2NO3(-)
Ba(2+) + SO4(2-) = BaSO4↓
CaCO3 -> CaO + CO2
CaO + H2O = Ca(OH)2
Ca(OH)2 + 2HCl = CaCl2 + 2H2O
Ca(OH)2 + 2H(+) + 2Cl(-) = Ca(2+) + 2Cl(-) + 2H2O
Ca(OH)2 + 2H(+) = Ca(2+) + 2H2O
CaCl2 + Na2CO3 = CaCO3↓ + 2NaCl
Ca(2+) + 2Cl(-) + 2Na(+) + CO3(2-) = CaCO3↓ + 2Na(+) + 2Cl(-)
Ca(2+) + CO3(2-) = CaCO3↓
2)2C4H10+13O2=8CO2+10H2O
3)C2H6+Cl2=C2H5Cl+HCl
4)C5H12- пентан